Changes in macrofauna bioturbation during repeated heatwaves mediate changes in biogeochemical cycling of nutrients - Kauppi, Laura; Göbeler, Norman; Norkko, Joanna; Norkko, Alf; Romero-Ramirez, Alicia; Bernard, Guillaume (Frontiers in Marine Science, 2023)
The increasing frequency and intensity of marine heatwaves (MHWs) observed worldwide entails changes in the structure and functioning of ecological communities. While severe and extreme heatwaves often have more destructive effects, the more subtle effects of moderate and strong heatwaves may nevertheless affect ecosystem functioning through complex, context-dependent linkages between different processes. Here we conducted a laboratory experiment to study the effects of repeated short-term, strong MHWs on macrofauna bioturbation and associated solute fluxes as a measure of ecosystem functioning using natural soft-sediment communities from the Baltic Sea. Our results showed changes in both bioturbation and biogeochemical cycling of nutrients following short-term, strong heatwaves, which seemed to contribute to an enhanced degradation of organic matter in the seafloor and an enhanced exchange of solutes across the sediment-water interface as well as increased sediment oxygen consumption. Following changes in these processes, the relative contribution of macrofauna and the environmental context to ecosystem functioning was altered. Our results highlight the potential of even shorter-term, strong MHWs of having system-wide impacts due to changes in the mechanistic process of bioturbation underpinning the biogeochemical cycling of nutrients. This study also highlights the need to measure a wide range of variables for a comprehensive understanding of the changes in functioning under disturbances, such as MHWs.